SPIONs as Nano-Theranostics Agents - Zarepour, Atefeh; Zarrabi, Ali.; Khosravi, Arezoo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This Brief introduces SuperParamagnetic Iron Oxide Nanoparticles (SPIONs), the different synthesis approaches, their applications in the field of diagnostics and treatment and finally as theranostic agents in cancer.
Introduction -- Iron oxide Nanoparticles -- Biomedical application -- Challenges and future prospects.
Keywords: Biomedical engineering; Biomaterials; Medicine -- Research; Biology -- Research; Microtechnology; Microelectromechanical systems; Cancer; Biomedical Engineering and Bioengineering; Biomaterials; Biomedical Research; Microsystems and MEMS; Cancer Biology